Development Research for Global Justice. Issue 1 (2nd January 2017) - Bigsten, Arne
Abstract : Is the global development agenda changing and, if so, what does this imply for development researchers? The following remarks first discuss our quest for global justice and relate this objective to the new Sustainable Development Goals (SDGs). Then I give my take on how the development of poor countries is determined and suggest what directions future research should take to support global justice through the development of poor countries. Considering aid as a principal tool to promote global justice, I conclude with a few comments about changes in the contemporary aid landscape and their implications for aid research.